O‘ZBEK TILIDA TURIZM TERMINLARINING MAVZUVIY GURUHLARI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article analyzes thematic groups of tourism terms in the Uzbek language.In the modern era of globalization, despite natural disasters, economic downturns, various conflicts, terrorist attacks, wars, etc., the growth of tourism is observed all over the world and tourism is treated as one of the fastest growing sectors of the economy. For this reason, new terms appear in the lexical layer of the language.
Keywords: ecotourism, hotel, travel agent.